TELAAH GAYA ARSITEKTUR MEDITERANIA DI INDONESIA - Freddy H. Istanto (DIMENSI (Journal of Architecture and Built Environment), 1999)
During the last decade of 1990' s, the style of architecture takes after the architectural style of Mediterranean. This style has invited a strong polemic against the name it bears. Is Mediterranean spanning the three continents appropriate of representing the name of Mediterranean-style ? This paper will discuss about the historical development of this Architectural style and its physical elements. Abstract in Bahasa Indonesia : Gaya arsitektur yang marak di Indonesia pada dasawarsa akhir tahun 1990-an adalah gaya arsitektur Mediterania. Gaya arsitektur ini mengundang polemik tentang nama yang disandangnya, apakah kawasan Mediterania yang meliputi tiga benua itu layak mewakili nama gaya arsitektur Mediterania ?. Makalah ini membahas perjalanan Gaya Arsitektur ini dan elemen-elemen fisikalnya. Kata kunci : gaya arsitektur Mediterania, elemen-elemen fisikal.